Interfacial engineering at hole transport layer and perovskite interface for efficient perovskite based light emitting diodes - Cahatian, Marinelle Jannica Sencio (Nanyang Technological University, 2022)
Due to its defect tolerant nature, high photoluminescence quantum yield, and narrow photoluminescence full width half maximum, organic inorganic halide perovskites have garnered significant attention especially for light emitting diodes application, the main focus of this project. Named after its crystal structure, it has an APbX3 structure where A is the organic or inorganic cation and X is the halide anions. Bulky organic cation can also be added into the structure to break the 3D [PbX6] octahedra network to form quasi 2D structures to enhance the carrier confinement in the system. Among various parameters, hole transport layer (HTL) and perovskite emitter interfaces are one of the most important parameters that heavily dictate the performance of perovskite-based light emitting diodes (PeLED). The interface quality influences both the interfacial defect density and the quality of bulk perovskite grown on top which are crucial for PeLED performances. Herein, interfacial engineering at HTL/perovskite interfaces were done by either introducing an electron blocking layer or increasing the halide ions at the interfaces. Poly(N,N′ -bis(4-butylphenyl)-N,N′ -bis(phenyl) benzidine) (poly-TPD) was used as an excellent hole transport material with the favourable energy levels and electron blocking capability. However due to its very hydrophobic nature, the need for surface modification was recognized. Various treatments were evaluated, i.e. Dimethylformamide solvent, Poly(9,9-bis(3’-(N,N-dimethyl)-N-ethylammoinium-propyl-2,7-fluorene)-alt-2,7-(9,9-dioctylfluorene))dibromide (PFNBr), Ultraviolet (UV) Ozone treatment and Argon plasma treatment. The changes on the optical, electrical, and interfacial properties upon treatments were characterized in depth. Amongst these 4 approaches, successful incorporation of Poly-TPD layer was achieved by UV Ozone treatment. In addition to that, an impressive external quantum efficiency (EQE) enhancement (~200%) was reflected by UV Ozone treated Poly-TPD devices as compared to the other devices. While pin holes in the perovskite emitter were still found in the current system, further optimization to eliminate them would guarantee an even higher EQE enhancement. Literatures indicate that halide-rich interfaces were useful to passivate uncoordinated Pb2+ interface defects which promote higher radiative recombination leading to efficient PeLED. Halide acids, i.e. Hydrochloric and Hydrobromic acid, were utilised and the effect of acid concentration on the physical, optical, and electrical properties of HTL were evaluated. Despite its potential, no significant improvement on the conductivity and device performance were found.